Heavy-slow resistance training in addition to an ultrasound-guided corticosteroid injection for individuals with plantar fasciopathy: a feasibility study - Henrik Riel (Pilot and Feasibility Studies, 2019)
Abstract Introduction Plantar fasciopathy, characterised by plantar heel pain, affects one in ten in a lifetime. Heavy-slow resistance training (HSR) is an emerging treatment, but it often takes considerable time before the effect starts to manifest. Combining HSR with a corticosteroid injection (known for its short-term pain relief) could potentially improve outcomes in both short and long term. As this combination is yet to be investigated, we aimed to evaluate the feasibility of combining HSR with a corticosteroid injection for individuals with plantar fasciopathy before investigating the efficacy in a clinical trial. Materials and methods We recruited 20 participants with plantar fasciopathy for this prospectively registered feasibility study (ClinicalTrials.gov: NCT03535896). Participants received an ultrasound-guided injection and performed heel raises on a step every second day for 8 weeks. To assess participant acceptability of the combined interventions and exercise compliance, we used a 7-point Likert scale dichotomised to “unacceptable” (categories 1–2) or “acceptable” (categories 3–7) and training diaries. Greater than or equal to 10/20 had to rate the combination “acceptable”, ≥ 15/20 had to perform ≥ 20 training sessions, and ≥ 15/20 had to start exercising ≤ 7 days after injection to confirm feasibility. Results Eighteen out of 20 rated the combination acceptable. Five training diaries could not be retrieved. Ten out of 15 participants performed ≥ 20 training sessions, and 15/15 started exercising ≤ 7 days after injection. Conclusions Based on participant acceptability and time to exercise start, combining HSR with corticosteroid injection is feasible and the efficacy should be investigated in a future trial. Due to loss of 5/20 training diaries, firm conclusions regarding exercise compliance could not be drawn. Trial registration ClinicalTrials.gov, NCT03535896